2020
DOI: 10.3171/2020.2.focus191002
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor treatment and mortality following nontraumatic subarachnoid hemorrhage: a nationwide electronic health record analysis

Abstract: OBJECTIVESubarachnoid hemorrhage (SAH) is a devastating cerebrovascular condition, not only due to the effect of initial hemorrhage, but also due to the complication of delayed cerebral ischemia (DCI). While hypertension facilitated by vasopressors is often initiated to prevent DCI, which vasopressor is most effective in improving outcomes is not known. The objective of this study was to determine associations between initial vasopressor choice and mortality in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…19 Finally, our recent work has demonstrated a beneficial association between phenylephrine use and the adverse outcome in this population. 20 Our machine learning predictive models from all six cases (Fig. 3 bottom panel) further confirmed that the phenylephrine use could associate with a reduced probability of adverse outcome after adjusting many other confounding factors in the predictive models.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…19 Finally, our recent work has demonstrated a beneficial association between phenylephrine use and the adverse outcome in this population. 20 Our machine learning predictive models from all six cases (Fig. 3 bottom panel) further confirmed that the phenylephrine use could associate with a reduced probability of adverse outcome after adjusting many other confounding factors in the predictive models.…”
Section: Discussionsupporting
confidence: 62%
“…Laboratory variables such as glucose (hyperglycemia), anion gap acidosis, renal function, and serum osmolality would also be expected to be associated with adverse clinical outcomes 19 . Finally, our recent work has demonstrated a beneficial association between phenylephrine use and the adverse outcome in this population 20 . Our machine learning predictive models from all six cases (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…To date, literature indicating a relationship between high-dose norepinephrine and the development of DCI is scarce. The reason for the rare reporting of adverse effects of norepinephrine on DCI may originate from the fact that many studies report starting to administer vasopressors after a delayed ischemic neurologic deficit or even DCI occurs [ 29 , 38 , 39 ]. However, patients admitted to our institution routinely receive norepinephrine for MAP maintenance right after successful aneurysm treatment (i.e., within 24 hours), which inherently minimizes this potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that excessive use of vasopressors comes with the risk of severe end organ damage, presumably caused by arteriolar and capillary vasoconstriction as well as peaks of systolic arterial blood pressure [28][29][30].…”
Section: Vasopressor Therapy After Intracranial Hemorrhagementioning
confidence: 99%
“…169,170 A more recent retrospective study showed an opposite result: phenylephrine was associated with reduced mortality in aSAH patients as compared to dopamine or norepinephrine. 171 An important limitation of this study was that a change of vasopressor occurred in 33% of patients during the same encounter of care, which was not accounted for in the statistical analysis. Dopamine is another vasopressor often used in studies investigating induced hypertension as treatment for DCI.…”
Section: Complications Of Induced Hypertensionmentioning
confidence: 98%